2004
DOI: 10.2516/ogst:2004042
|View full text |Cite
|
Sign up to set email alerts
|

Development of Natural Gas Demonstrator Based on an Urban Vehicle with a Down-Sized Turbocharged Engine

Abstract: -Développement d'un démonstrateur gaz naturel sur la base d'un véhicule urbain doté d'un moteur suralimenté-L'objectif principal de ce projet est de confirmer le potentiel du gaz naturel en tant que carburant, pour les applications urbaines notamment. Un véhicule de démonstration utilisant uniquement le CNG (compressed natural gas) comme carburant à été développé, en se basant sur un véhicule urbain existant. Le but est de parvenir à des émissions de CO 2 faibles, avec un niveau maximal de 100 g/km sur le cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Similar works [29,30] prove that part of the fuel injected to the intake port will generate wall wetting in the cold start. Tilagone and Venturi [31] changed a gasoline engine of vehicle application to a natural gas engine to evaluate the performance and emission of the engine, and they demonstrated that natural gas contributes to a remarkable decline in emission compound, meaning 50% less UHC compared to a gasoline engine. The main reason for this drop is the limited oil film adsorption-desorption phenomenon.…”
Section: Difference Between the Influence Of Gas And Liquid Fuel In Fmentioning
confidence: 99%
“…Similar works [29,30] prove that part of the fuel injected to the intake port will generate wall wetting in the cold start. Tilagone and Venturi [31] changed a gasoline engine of vehicle application to a natural gas engine to evaluate the performance and emission of the engine, and they demonstrated that natural gas contributes to a remarkable decline in emission compound, meaning 50% less UHC compared to a gasoline engine. The main reason for this drop is the limited oil film adsorption-desorption phenomenon.…”
Section: Difference Between the Influence Of Gas And Liquid Fuel In Fmentioning
confidence: 99%
“…The volumetric efficiency loss due to the displacement of air by gaseous fuels can be compensated by boosting the induced air, thereby increasing the breathing efficiency of the engine [219]. The volumetric efficiency of gaseous-fuel engines is also affected by the lack of evaporative cooling that is associated with liquid fuels [220,221]. In terms of the fuel properties, CNG has a lower laminar flame speed and a lower energy density compared to its liquid counterpart, as shown in Table 7.…”
Section: Effect Of Boost Pressurementioning
confidence: 99%
“…In order to reach very low CO 2 emissions IFP has developed a Compressed Natural Gas (CNG) hybrid Smart 600 cc Smart engine [24]. To improve torque at low speed, a mild-hybrid approach based on a 3 kW starter alternator supplies extra-power for peak load conditions.…”
Section: • Compressed Natural Gas Light Hybrid Enginementioning
confidence: 99%